APLICAÇÃO DO RAPID LEAN CONSTRUCTION-QUALITY RATING MODEL EM OBRAS PÚBLICAS - Brandão, Evandro Luiz; Pacheco, Ana; Wons, Luciano; Freitas, Maria do Carmo Duarte (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The concept of lean construction has been in development since its inception by Koskela in 1992. The concept follows basic preinciples that put the customer's needs in focus, reduce wastes, diminish activities that do not generate value, trim cycle times, increase process transparency and aims at continuous improvement. With this is mind, it is needed to evaluate the implementation of the lean philosophy in companies and worksites. With the help of flows of information, Hofacker et al. (2018) conceived a quantitative scale to grade the use of the lean philosophy in an enterprise through a questionnaire. The questionnaire was applied to five different construction sites of public works in Brazil and their lean grade was evaluated. The conclusion was that the concepts of the lean philosophy were present in them but could be greatly improved.